Non-prescription dispensing of veterinary medicines for treating mastitis in dairy cattle among non-veterinary personnel in selected districts of Zambia - Bwalya, Amon; M’kandawire, Ethel; Pyatt, Alison; Prince, Catrina; Gilbert, Claire; Muma, John Bwalya; Mudenda, Steward (Frontiers in Veterinary Science, 2026)
ObjectivesVeterinary antibiotics are vital for managing bacterial infections in animals and preventing zoonotic transmission through animal-derived foods, direct contact, or the environment. However, their misuse and overuse contribute to the emergence and spread of antimicrobial resistance (AMR) across humans, animals, and ecosystems. This study assessed the dispensing practices of non-veterinary personnel regarding veterinary medicines used in dairy cattle in selected districts of Zambia. Specifically, it estimated the prevalence of non-prescription dispensing of antibiotics for treating mastitis and identified the most commonly dispensed antibiotic classes.MethodsA cross-sectional study was conducted between September 2024 and June 2025 among 220 veterinary medicine dispensers in Lusaka, Chisamba, Kafue, Chongwe, Monze, and Choma districts. Data were collected using a simulated farmer (mystery shopper) approach to document veterinary antibiotics and other medicines dispensed for treating mastitis in dairy cattle at retail pharmacies and agro-veterinary shops.ResultsOf the 220 outlets, 74 (33.6%) were agro-veterinary shops and 146 (66.3%) retail pharmacies. Overall, 126 outlets did not stock veterinary medicines for mastitis. Among the 94 that did, 85 (90.4%) dispensed antibiotics and 9 (9.6%) dispensed other medicines without a prescription. Of the 134 veterinary medicines dispensed, 74.6% (n = 100) were antibiotics, followed by anti-inflammatories (11.2%), supplements (7.5%), hormones (4.5%), and antiparasitics (2.2%). Common antibiotic classes included penicillins, aminoglycosides, tetracyclines, and cephalosporins. Only 53.2% of attendants asked about symptoms, and among them, 54.7% provided a tentative diagnosis. Few inquired about prior treatment (8.5%), advised on disease progression (19.1%), or referred the simulated farmer to a veterinarian (12.3%). While 74.5% communicated the correct route of administration, only 63.8% mentioned dosage frequency, and 58.5% specified treatment duration.ConclusionNon-prescription dispensing of veterinary antibiotics for mastitis by non-veterinary personnel is widespread, posing significant AMR risks to animal, human, and environmental health. Strengthened regulatory oversight, antimicrobial stewardship training, and collaboration between veterinarians and drug outlet owners are essential to promote responsible antibiotic use and curb AMR.